RANCANG BANGUN MESIN PRES BATAKO OTOMATIS MENGGUNAKAN SISTEM ELEKTRTO PNEUMATIK BERBASIS PLC DAN HMI - Juliandi Rachman, Muhammad (Electrical Network Systems and Sources, 2024)
The high rate of infrastructure development in Pontianak City and Kubu Raya Regency will also impact the demand for construction materials, one of which is "batako" as the main material in building walls for houses or other structures. The main objective of this research is to develop a pressing machine that can enhance efficiency and accuracy in the "batako" manufacturing process. The research begins with field observations, data processing, component design and calculation, tool and material preparation, assembly and tool manufacturing, programming, data collection from the working process, and conclusion of system analysis. This automatic "batako" pressing machine takes 34.36 seconds to produce 4 pieces of "batako" in one pressing cycle. This process is significantly faster and more efficient compared to manual "batako" production, which takes about 1 minute to produce one piece. The "batako" pressing machine features a protection system that serves as a crucial step in ensuring safety and operational efficiency. By stopping and returning the ongoing process to avoid further errors, this system excels in automatically restoring the machine to its initial condition in emergency situations, thus preventing damage to machine components and enhancing operator safety. Moreover, this system helps maintain production efficiency and consistency by minimizing downtime due to operational errors.